Nickel Extraction from Morowali Laterite Ore with Combination of Sulfuric Acid (H2SO4) and Nitric Acid (HNO3) - Mujahida Mustari; Daud K. Walanda; Mery Napitupulu; Sri H. V. Pulukadang (Jurnal Akademika Kimia, 2024)
Nickel is a very important metal. The nickel reserves in Indonesia are very large, but there is no dedicated process that uses only nickel ore as a raw material. The process of separating nickel from impurities is carried out by leaching with a sulfuric acid-nitric acid solution. The research design was developed using the Taguchi Larger-the-Better method to optimize nickel extraction. In the leaching stage, nickel is extracted from the ore by dissolving it in an acid medium. The variables examined in this study were the mixture ratio, temperature, and leaching time. The extracted filtrate was analyzed using Atomic Absorption Spectrophotometry (AAS). The results of the Taguchi analysis showed that the optimal conditions for the leaching process were obtained with a mixture ratio of 2:1, a temperature of 60 °C, and a leaching time of 12 hours, yielding a concentration of 10.559 ppm and a recovery of 2.49%.